Penerapan Undang-Undang Batas Minimal Usia Perkawinan Dan Dampaknya Dalam Masyarakat - Abdur Rohman; Ita Rahmania Kusumawati (Hukum Keluarga Islam IAIN LANGSA, 2022)
The marriage law regarding the minimum age for marriage has been updated to 19 years to prevent early marriage, protect children's rights, and reduce the divorce rate. In the Jombang District Religious Court, the increase in the minimum age for marriage has resulted in an increase in the number of dispensations for marriage. This study discusses how the latest law regarding the minimum age limit for marriage is implemented and the impact of this law. This research is an empirical research with a qualitative approach and the primary data collection method is through interviews with judges at the Religious Court of Jombang Regency. The results of this study found that the application of Law Number 16 of 2019 in the Jombang Regency Religious Court was not optimal. Evidenced by the significant increase in cases after the passing of the law. This is caused by factors of education and public awareness that is still low. This law is an attempt by the government to reduce the number of early marriages that have occurred recently. However, the implementation of the Law on limiting the age for marriage is constrained by the low level of public education and the economic level of some people who are still below average. As a recommendation, a concrete step is needed so that the implementation of the law on limiting the age of marriage becomes optimal, including the empowerment of regional officials, religious leaders and community leaders.